2003
DOI: 10.1086/368310
|View full text |Cite
|
Sign up to set email alerts
|

A Triple Radio Continuum Source Associated with IRAS 16547–4247: A Collimated Stellar Wind Emanating from a Massive Protostar

Abstract: We report the discovery, made using the Australia Telescope Compact Array, of a triple radio source toward IRAS 16547À4247, a luminous infrared source with a bolometric luminosity of 6:2 Â 10 4 L . The radio source shows an almost linear structure consisting of a compact central object and two outer lobes separated by about 20 00 , located symmetrically to the central source. The radio emission from the lobes has spectral indices of À0.61 and À0.33, characteristic of nonthermal emission. The emission from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
135
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(160 citation statements)
references
References 51 publications
19
135
0
3
Order By: Relevance
“…They include IRAS 18162−2048 (L ∼ 1.7 × 10 4 L ; Martí et al 1993), Cepheus A HW2 (L ∼ 1 × 10 4 L ; Rodríguez et al 1994), IRAS 20126+4104 (L ∼ 1.3 × 10 4 L ; Cesaroni et al 1997), G192.16−3.82 (L ∼ 3 × 10 3 L ; Shepherd et al 1998Shepherd et al , 2001Devine et al 1999), and W75N, which contains several molecular and HH outflows powered by at least four late-to early-B protostars (Shepherd et al 2003). There is only one YSO with L > 2 × 10 4 L that is associated with a highly collimated jet (IRAS 16547−4247, L ∼ 6.2 × 10 4 L ; Garay et al 2003;Rodríguez et al 2005Rodríguez et al , 2008Brooks et al 2007). Two other luminous YSOs, IRAS 18089−1732 (L ∼ 3.2 × 10 4 L ; Beuther & Walsh 2008) and G331.51−0.10 (L ∼ 1×10 5 L ; Bronfman et al 2008), are associated with radio continuum sources with spectral indices characteristic of collimated stellar winds, but the angular resolution of the observations is insufficient to resolve the jet/flow morphology.…”
Section: Introductionmentioning
confidence: 99%
“…They include IRAS 18162−2048 (L ∼ 1.7 × 10 4 L ; Martí et al 1993), Cepheus A HW2 (L ∼ 1 × 10 4 L ; Rodríguez et al 1994), IRAS 20126+4104 (L ∼ 1.3 × 10 4 L ; Cesaroni et al 1997), G192.16−3.82 (L ∼ 3 × 10 3 L ; Shepherd et al 1998Shepherd et al , 2001Devine et al 1999), and W75N, which contains several molecular and HH outflows powered by at least four late-to early-B protostars (Shepherd et al 2003). There is only one YSO with L > 2 × 10 4 L that is associated with a highly collimated jet (IRAS 16547−4247, L ∼ 6.2 × 10 4 L ; Garay et al 2003;Rodríguez et al 2005Rodríguez et al , 2008Brooks et al 2007). Two other luminous YSOs, IRAS 18089−1732 (L ∼ 3.2 × 10 4 L ; Beuther & Walsh 2008) and G331.51−0.10 (L ∼ 1×10 5 L ; Bronfman et al 2008), are associated with radio continuum sources with spectral indices characteristic of collimated stellar winds, but the angular resolution of the observations is insufficient to resolve the jet/flow morphology.…”
Section: Introductionmentioning
confidence: 99%
“…These shocks can accelerate particles that, in turn, can produce gamma rays trough inverse Compton (IC) scattering of infrared (IR) photons, relativistic Bremsstrahlung, or inelastic proton-proton collisions, if protons are accelerated as well. In some cases non thermal radio lobes and jets have Table 6 is available in electronic form at http://www.aanda.org been observed, indicating the presence of relativistic electrons that produce synchrotron radiation (Garay et al 2003;CarrascoGonzález et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…which is a typical value for massive YSOs (Garay et al 2003). On the other hand, if we assume that the continuum emission from NTT source #8 has an optically-thin free-free component with flux in the cm wavelengths of the order of 10 mJy (the total flux of the entire radio source at 6 cm is ∼80 mJy), and an electron temperature of 10 4 K for the ionized gas, we find that an ionizing photon flux of N i ∼ 5 × 10 47 s −1 (Carpenter et al 1990) is required to maintain the ionization.…”
Section: Discussionmentioning
confidence: 93%
“…Up to now, only a few massive young stellar objects (massive YSOs or MYSOs) are related to collimated jets mapped at the radio range, such as the Serpens sources (Rodríguez et al 1989), HH 80-81 (Martí et al 1993), and IRAS 16547−4247 (Garay et al 2003). Garay et al found this last object to be a triple quasi-linear radio source, that shows non-thermal indices at the lobes.…”
Section: Introductionmentioning
confidence: 99%